FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN DAN SIKAP IBU DALAM PEMBERIAN MAKANAN SEHAT DENGAN STATUS GIZI ANAK - RAHMAYANI, SRI TANTI (Kos Globalindo Group, 2021)
This study aims to determine: 1) the knowledge of mothers in providing healthy food; 2) mother's attitude in giving healthy food; 3) the nutritional status of children at SDN Beteng 1; and 4) the relationship between mother's behavior in giving healthy food with the nutritional status of children in grade III, IV, V at SDN 2 Sukamulya. This type of research is correlational with a quantitative approach. The study was conducted in December 2017 - August 2018. The population in this study were 119 students in grade III, IV, V at SD Negeri 2 Sukamulya. Sampling with proportionate stratified random sampling of 89 respondents. Data collection using a questionnaire. The validity of the instrument using expert judgment and Product Moment correlation, reliability with Croncbach's Alpha. The data analysis techniques were descriptive analysis, analysis requirements test and hypothesis testing.The results showed that: (1) the knowledge of mothers in giving healthy food was in the very high category of 49 students (55.1%), the high category was 37 students (41.6%), the low category was 3 students (3 , 4%), and in the very low category 0 students (0%). (2) the attitude of mothers in providing healthy food was in the very high category of 61 student mothers (68.5%), the high category was 28 students (31.5%), the low category was 0 students (0%), and the high category was 0 students (0%). very low as many as 0 students (0%). (3) the nutritional status of children in grades III, IV, and V at SDN 2 Sukamulya in the good category was 67 students (75.3%), malnutrition was 15 students (17%), and malnutrition was 7 students (8%) . 1) hypothesis testing shows that the knowledge of mothers in providing healthy food to the nutritional status of children gives an effective contribution (r2) of 0.59. 2) the attitude of the mother in giving healthy food to the nutritional status of the child gave an effective contribution (r2) of 0.47.